Pilot project “Improvement of medical care for patients with chronic heart failure”: results of the first stage - P. M. Murtazalieva; E. V. Karelkina; A. A. Shishkova; V. V. Zaitsev; N. E. Zvartau; O. M. Moiseeva (Российский кардиологический журнал)
Aim. To analyze congestive heart failure management in the clinical practice of the city emergency hospital in order to develop new strategies of improving health care program for patients with chronic heart failure (CHF).Material and methods. We reviewed 343 cases of hospitalization due to CHF decompensation. 88% of patients had NYHA Class III – IV on admission. The quality of care was assessed according to criteria approved by the Ministry of Health of Russian Federation and the Society of experts in heart failure.Results.Despite the fact that ECG and chest X-ray were performed in almost 100% of patients, echocardiography was performed only in 64% of cases, and Holter monitoringwas done in only 3%. Standard laboratory tests included determination of serum potassium and sodium concentrations in only 15% and 14% of cases. The levelsof serum lactate dehydrogenase, alkaline phosphatase and γ-glutamyl transpeptidase were estimated in less than 5% of patients. 94% of patients received beta-blockers, 93% angiotensing-converting enzyme inhibitors/angiotensin type II receptor blockers, 74% mineralocorticoid receptor antagonists and 88% diuretics. It should be noted that 48% of patients received parenteral diuretics before discharge from the hospital and were not adapted to receive oral diuretics. Only 13% of patients were evaluated for weight loss. At discharge, NYHA Class III - IV had 38% of patients. Conclusions. Despite the improvement in the clinical condition of patients during hospitalization, we identified factors that may adversely affect the effectiveness of care for patients with CHF. At the same time frequency of readmissions is determined by the insufficient continuity of outpatient and inpatient care. Therefore, development of the automated system for obtaining, integrating, storing and processing medical information will contribute to the improvement of medical care for patients with CHF.